Estrategias para una sucesión exitosa en la empresa familiar = Strategies for a sucessuful succession in family business. - García, Mayra E. (Universidad Autónoma de Nuevo León, 2007)
Abstract. This study has the objective to propose a group of strategies to help the Family Business Manager to solve the succession problems; by using these strategies the family business can conquer a transition power that creates the most wealth posible to the business and to the familiy. This study is presented as a descrptive research, with basis on the most recently research about succession problems on family business. The Familiy Business Managers who want that business still belongs to familiy have the obligation of developing a succession plan that allows the company continue being competitive when family business manager leaves the company. The strategies included in this study must be promoted by the Family Business Manager who must take care of leading the directive team to sucessuful power change. The strategies proposed in this study are: Creating a Family Business Conseil; Choosing the succesor from an analitical point of view; Get pschicologist support in the succesion period; To create a Business Society; Partial Retirement of Director; An adequate compensation management; Open communication among all the members; and a provisional management.